2016
DOI: 10.1002/hon.2338
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hemolytic anemia after nivolumab treatment in Hodgkin lymphoma responsive to immunosuppressive treatment. A case report

Abstract: The patients with refractory Hodgkin lymphoma have a poor prognosis. The nivolumab, an IgG4 monoclonal antibody inhibiting the program death 1 pathway has recently demonstrated its efficacy and its safety in patients with heavily pretreated refractory Hodgkin lymphoma. The side effects of this immunotherapy include autoimmune-like syndromes. A 75-year-old woman with no significant comorbidities was treated by nivolumab (3 mg/kg every 2 wk) as a third-line treatment for refractory Hodgkin lymphoma. A clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 8 publications
1
28
0
3
Order By: Relevance
“…AIHA post-nivolumab therapy appears to be a warm AIHA and is commonly mediated through IgG [3, 5], though IgG and C3 were both positive in one case [4]. Our case was exclusively mediated through C3, and IgG was negative.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…AIHA post-nivolumab therapy appears to be a warm AIHA and is commonly mediated through IgG [3, 5], though IgG and C3 were both positive in one case [4]. Our case was exclusively mediated through C3, and IgG was negative.…”
Section: Discussionmentioning
confidence: 72%
“…AIHA developed after 8 cycles of nivolumab and responded to short course of steroids. Tardy et al [5] reported a case of AIHA in a patient who received nivolumab in the third line for relapsed Hodgkin's lymphoma. AIHA developed after 2 cycles of nivolumab and responded to prolonged course of steroids (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei der AIHA nach einer Nivolumab-Therapie scheint es sich um eine Wärmeantikörper-AIHA zu handeln, die in der Regel durch IgG vermittelt wird [3,5], wobei in einem Fall sowohl der IgG-als auch der C3-Test positiv ausfielen [4]. In unserem Fall war C3 der ausschließliche Mediator; der IgG-Test war negativ.…”
unclassified
“…In allen berichteten Fällen erhielten die Patienten Nivolumab entweder in der zweiten oder in der dritten Therapielinie. Die Anämie trat in 2 Fällen nach 2 Zyklen Nivolumab auf [5], in einem Fall nach 5 Zyklen [3] und in einem Fall nach 8 Zyklen [4]. Eine Nivolumabassoziiert AIHA kann also in jeder Therapielinie au treten, entwe- …”
unclassified